Escalation of conflict in FMCG industry: a negotiation case - Pestana, João de Freitas Martins Gonçalves (2015)
This work project develops a case-study to be used in Negotiation courses, both in Masters programs and in executive education workshops. The case-study is based on a real-life negotiating situation in Belgium between Unilever, the second largest Fast Moving Consumer Goods (FMCG) company in the world, and Delhaize, one of the most important Belgium’s retailers, with a significant international presence. We also present an analysis of the negotiation based on relevant literature. First, a brief literature review is presented about how to deal with multiple-issue negotiations and how to deal with processes of escalation of conflict. These concepts are then applied to the analysis of the case-study.